Investigation on Unmanned Aerial Vehicle (UAV): An Overview - Vaigandla, Karthik Kumar; Thatipamula, Sravani; Karne, Radha Krishna (IRO Journal on Sustainable Wireless Systems, 2022)
Unmanned Aerial Vehicles (UAVs) are becoming increasingly popular these days. One among the major technological developments of today are UAVs or drones. The coordination and coverage capabilities of large clusters of UAVs, or their cooperative capabilities for such goals as terrain mapping, make them of particular interest. This paper explores the use of unmanned aerial vehicles in smart and modern cities in depth. Future wireless networks will likely include UAVs to facilitate wireless broadcasting and support high-speed transmissions. Various layer techniques are discussed in this paper. Moreover, an overview of the latest UAV communication technologies and network topologies has been presented. Military and commercial applications have attracted a lot of interest in unmanned aerial vehicles. Due to their low cost and flexible deployment, UAVs are considered valuable in 5G and 6G networks due to their communication capabilities. Like aerial base stations, relays, or mobile users in cellular networks, UAVs can provide airborne wireless coverage in a variety of ways. Wireless links can only be established temporarily with UAVs. A great challenge is to extend UAV communication’s lifetime and develop low-power, green UAV communication. A comprehensive study of green UAV communications has been presented in this paper. Furthermore, an overview of UAV applications is also illustrated. Additionally, some promising research topics and methods are being discussed.